Impact of visceral metastases on outcome to abiraterone after docetaxel in castration-resistant prostate cancer patients. (November 2015) - Conteduca, Vincenza; Caffo, Orazio; Fratino, Lucia; Lo Re, Giovanni; Basso, Umberto; D'Angelo, Alessandro; Donini, Maddalena; Verderame, Francesco; Ratta, Raffaele; Procopio, Giuseppe; Campadelli, Enrico; Massari, Francesco; et al.
Background: The objective of this study was to analyze the impact of visceral metastases in castration-resistant prostate cancer (CRPC) treated with abiraterone.Materials & methods: All CRPC patients received abiraterone 1000 mg daily plus prednisone 10 mg orally daily. Liver and lung metastases were considered as visceral metastases.Results: Of 265 CRPC patients, 49 had visceral metastases. Results on progression-free survival were not significantly different in patients with or without visceral metastases. Conversely, the median overall survival between the two groups was 12.4 and 18.5 months (p = 0.01), respectively, and median overall survival of patients with liver-only disease versus other sites was 10.5 versus 18.5 months (p = 0.006), respectively.Conclusion: Visceral disease appears to be an important predictor of clinical outcome in CRPC patients treated with abiraterone.